“... E eu pensei: o que estou fazendo aqui?!” homens egressos do curso de pedagogia: estabelecimento e deslocamento na profissão. - (:unkn) unknown (Universidade Federal de Goiás, 2017)
The objective of this research was to understand the reasons that led these graduates to establish themselves or to become part of the Pedagogy course of the Federal University of Goiás - Regional de Catalão (UFG / RC), formed between 1991 and 2014. To move from the area of practice allowed by the profession of pedagogue. The unfolding of the general objective allowed to broaden the discussion about the historical trajectory of the Pedagogy course, which includes the change in the qualifications, in Brazil and in Catalão, articulating the latter with the own history of implantation of the advanced Campus of the UFG in that city. This work also discussed "gender" and "masculinity", trying to understand the point of view of the egresses about the relations between the genders and how these are in the field of their professional choices. The research made it possible to undertake a quantitative and qualitative mapping of the men graduating from the Pedagogy course of the UFG / RC in the last decades, as well as the promotion of a bibliographical analysis about the male sex in the education of young children and the feminization of the teaching profession. For documentary analysis, institutional documents were used, such as the Political pedagogical projects of the Pedagogy course and the production of interviews with the graduates participating in the research. From a methodological point of view, we chose case studies, through interviews and also quantification and analysis of the data. At the end of the research, we found that despite the difficulties encountered, a significant number of graduates remained in the area of activity of the pedagogue.
"... And i thought: what am i doing here ?!" homeless people of the course of pedagogy: establishment and displacement in the profession.
Keywords: Estabelecimento; Deslocamento; Gênero; Masculinidade; Pedagogo; Establishment; Displacement; Genre; Masculinity; Pedagogist; Egresso; Egress; CIENCIAS HUMANAS::EDUCACAO